2015
DOI: 10.1002/jeab.175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of display timing on change blindness in pigeons (Columba livia)

Abstract: Change blindness is a phenomenon in which even obvious changes in a visual scene may go unnoticed. Recent research has indicated that this phenomenon may not be exclusive to humans. Two experiments investigated change blindness in pigeons, using a variant of the widely-used flicker task to investigate the influence of display timing on change blindness. Results indicate that the duration of time during which a stimulus display is visible influences change detection accuracy, with the effect due to additional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…Overall, subjects detected changes significantly more accurately with the longest search display (5,000 ms), followed closely by the second longest search display (2,500 ms), than the shorter search displays (250 ms, 500 ms, 1,000 ms). These results are in line with change detection findings from humans (Pashler, 1988), chimpanzees (Tomonaga & Imura, 2015), and pigeons (Herbranson & Davis, 2016) and suggest that the monkeys performed better when they had longer to encode the stimulus into their visual working memory, likely resulting in a stronger memory trace of the stimulus than when presented with shorter search displays.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, subjects detected changes significantly more accurately with the longest search display (5,000 ms), followed closely by the second longest search display (2,500 ms), than the shorter search displays (250 ms, 500 ms, 1,000 ms). These results are in line with change detection findings from humans (Pashler, 1988), chimpanzees (Tomonaga & Imura, 2015), and pigeons (Herbranson & Davis, 2016) and suggest that the monkeys performed better when they had longer to encode the stimulus into their visual working memory, likely resulting in a stronger memory trace of the stimulus than when presented with shorter search displays.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, pigeons (Columba livia) have also been found to exhibit change blindness. Herbranson and Davis (2016) varied the duration of the search display between 15 ms and 125 ms, with a 30-ms mask used on half of all trials. They found that pigeons performed better with no mask and longer search displays.…”
mentioning
confidence: 99%
“…No que se refere às pesquisas empíricas acerca do fenômeno da cegueira de mudança, apesar de também existirem trabalhos em uma perspectiva operante, sobretudo com animais (Herbranson, Trinh, Arand, Barker, Pratt, 2014;Herbranson, 2015;Herbranson & Davis, 2016), nas pesquisas com humanos, os estudos são amplamente baseados em uma perspectiva cognitivista. Um dos procedimentos mais tipicamente empregados na investigação desse fenômeno é o flicker task, anteriormente mencionado, que pode ser traduzido como tarefa de imagens intermitentes (e.g., Cohen, 2009;Maccari, et al, 2012;Rensink et.…”
Section: Fundamentação Teóricaunclassified
“…The extent of the similarity of nonhuman animal memory systems and human memory systems is largely unexplored. Comparative research has demonstrated qualitative similarities between the working memory of humans and of nonhuman primates, and to a lesser extent, pigeons (Elmore et al, 2011;Gibson et al, 2011;Herbranson & Davis, 2016;Wright et al, 2010). Studies using nonhuman primates have reported evidence for iconic memory at short delays, and the temporal boundaries of iconic and working memory were comparable with those of humans (Keysers et al, 2005;Truppa et al, 2014).…”
mentioning
confidence: 99%